2020
DOI: 10.3390/atoms8020018
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Developments of the Atomic Database on Rare-Earths at Mons University (DREAM)

Abstract: The main purpose of the Database on Rare Earths At Mons University (DREAM) is to provide the scientific community with updated spectroscopic parameters related to lanthanide atoms (Z = 57–71) in their lowest ionization stages. The radiative parameters (oscillator strengths and transitions probabilities) listed in the database have been obtained over the past 20 years by the Atomic Physics and Astrophysics group of Mons University, Belgium, thanks to a systematic and extensive use of the pseudo-relativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…The wavelengths, transition probabilities and oscillator strengths were then computed for the spectral lines involving all the Ce II atomic states obtained in the CV1 model. When comparing these results with the data taken from the DREAM database (Quinet & Palmeri 2020), we found a good overall agreement, i.e. within 5% for the wavelengths and within 30% for the transition rates.…”
Section: Ce IIsupporting
confidence: 65%
See 3 more Smart Citations
“…The wavelengths, transition probabilities and oscillator strengths were then computed for the spectral lines involving all the Ce II atomic states obtained in the CV1 model. When comparing these results with the data taken from the DREAM database (Quinet & Palmeri 2020), we found a good overall agreement, i.e. within 5% for the wavelengths and within 30% for the transition rates.…”
Section: Ce IIsupporting
confidence: 65%
“…In Figures 14, 15 and 16, we show the expansion opacities calculated by using transition rates of Ce II, Ce III, and Ce IV, respectively. The blue lines correspond to the results deduced from the best atomic data computed in the present paper, while the red lines in Figures 14 and 15 display the results obtained using the radiative parameters listed in the DREAM database (Quinet and Palmeri 2020). When looking at Figure 14 it can be clearly observed that, for Ce II, the behaviour of opacity is similar whether we use our atomic data or those taken from DREAM, both curves having a maximum at about 4400 Å (4355 Å using our data and 4395 Å using DREAM).…”
Section: Opacities For Ce Ii-iv Ionsmentioning
confidence: 59%
See 2 more Smart Citations
“…The Database of Rare Earths At Mons University (DREAM) contains information concerning the radiative parameters (wavelengths, transition probabilities and oscillator strengths) for more than 72,000 spectral lines belonging to the lower ionisation stages of lanthanide elements (Z = 57 to 71), from neutral to triply ionised species. This database, originally created by Biémont et al [45] and recently updated by Quinet and Palmeri [39], is hosted by Mons University (http://hosting.umons.ac. be/html/agif/databases/dream.html).…”
Section: Dream-desirementioning
confidence: 99%